City and good life: the determination of the ethical nature of politics in book i of Aristotle’s Politics - Tavares Simões Estelita, Izabella (2024)
The main purpose of this article is to show the radically normative political conception developed by Aristotle in Book I of Politics, a conception that determines life in the city as a fundamental condition for the achievement of human excellence or virtue (ἀρετή). It is a question, therefore, of investigating how the philosopher thinks of the polis as a form of community (κοινωνία) that aims not only to ensure the necessary material and economic conditions for basic human living (ζῆν), but also to provide man with a higher locus in which he can actualize the good life (εὖ ζῆν), that is, the life understood as the realization of virtue and rationality that are proper to him, which leads to a vigorous subordination of politics to the demands of morality.